Cognitive skills, non-cognitive skills, and family background: Evidence from sibling correlations - Silke Anger; Daniel D. Schnitzlein (Bamberg University, Bamberg Economic Research Group (BERG), 2016)
This paper estimates sibling correlations in cognitive and non-cognitive skills to evaluate the importance of family background for skill formation. Based on a large representative German dataset including IQ test scores and measures of non-cognitive skills, a restricted maximum likelihood model indicates a strong relationship between family background and skill formation. Sibling correlations in non-cognitive skills range from 0.22 to 0.46; therefore, at least one-fifth of the variance in these skills results from shared sibling-related factors. Sibling correlations in cognitive skills are higher than 0.50; therefore, more than half of the inequality in cognition can be explained by shared family background. Comparing these findings with those in the intergenerational skill transmission literature suggests that intergenerational correlations capture only part of the influence of family on children's cognitive and non-cognitive skills, as confirmed by decomposition analyses and in line with previous findings on educational and income mobility.
Keywords: J24; J62; 330; sibling correlations; family background; non-cognitive skills; cognitive skills; intergenerational mobility